A Novel Nitrobenzoate Microtubule Inhibitor that Overcomes Multidrug Resistance Exhibits Antitumor Activity - Zheng, Yan-Bo (Sci Rep, 2016)
Multidrug resistance is a major limitation for microtubule-binding agents in cancer treatment. Here we report a novel microtubule inhibitor (2-morpholin-4-yl-5-nitro-benzoic acid 4-methylsulfanyl-benzyl ester, IMB5046), its cytotoxicity against multidrug-resistant cell lines and its antitumor efficacy in animal models. IMB5046 disrupted microtubule structures in cells and inhibited purified tubulin polymerization in vitro. It bound to the colchicine pocket of tubulin. IMB5046 displayed potent cytotoxicity against multiple tumor cell lines with an IC(50) range of 0.037–0.426 μM. Notably, several multidrug-resistant cell lines which were resistant to colchicine, vincristine and paclitaxel remained sensitive to IMB5046. IMB5046 was not a P-glycoprotein substrate. IMB5046 blocked cell cycle at G2/M phase and induced cell apoptosis. Microarray assay indicated that the differentially expressed genes after IMB5046 treatment were highly related to immune system, cell death and cancer. In a mouse xenograft model IMB5046 inhibited the growth of human lung tumor xenograft by 83% at a well-tolerated dose. It is concluded that IMB5046 is a tubulin polymerization inhibitor with novel chemical structure and can overcome multidrug resistance. It is a promising lead compound for cancer chemotherapy, especially for treatment of multidrug-resistant tumors.